The Effect Of Using Mondly Application As Platform Teaching Basen On AI To Improve English Vocabulary Mastery At Junior High School 04 Bengkulu - Regy Pristiawan; Ferri Susanto; Anita Anita (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This research aimed to analyze the effect of using the Mondly application based on Artificial Intelligence (AI) on improving English vocabulary mastery among seventh-grade students at SMP Negeri 04 Bengkulu. The main problem was the students’ low vocabulary ability, which resulted from traditional teaching methods and the lack of interactive learning media. To address this issue, the study employed a quasi-experimental method using a Non-Equivalent Control Group Design that involved two classes: VII.1 as the experimental group and VII.2 as the control group. Multiple-choice test instruments were administered as pre-tests and post-tests to measure students’ vocabulary mastery before and after treatment. The results show that the experimental class experiences a significant improvement compared to the control class. These findings indicate that the Mondly application is effective as an AI-based learning platform for enhancing students’ vocabulary mastery and creates a more interactive and engaging learning environment for seventh-grade learners.